2019
DOI: 10.1177/1553350619861563
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Training, Used-Hand, and Experience on Endoscopic Surgery Skills in an Educational Computer-Based Simulation Environment (ECE) for Endoneurosurgery Training

Abstract: Today, virtual simulation environments create alternative hands-on practice opportunities for surgical training. In order to increase the potential benefits of such environments, it is critical to understand the factors that influence them. This study was conducted to determine the effects of training, used-hand, and experience, as well as the interactions between these variables, on endoscopic surgery skills in an educational computer-based surgical simulation environment. A 2-hour computer-based endoneurosur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Also, cadaveric dissection is the gold standard for training neurosurgeons because it allows surgical techniques to be demonstrated, provides a unique experience with a wide range of sensory inputs, and creates necessary surgical skills ( 12 , 13 ). These skills include depth perception, 2D and 3D vision orientation, sensitive movements in limited environments ( 14 ), bimanual coordination, and hand-eye coordination ( 15 , 16 ). In fields such as chess, music, sports, and mathematics, studies on human performance have shown that attaining an expert performance level requires about 10,000 hours of focused practice ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, cadaveric dissection is the gold standard for training neurosurgeons because it allows surgical techniques to be demonstrated, provides a unique experience with a wide range of sensory inputs, and creates necessary surgical skills ( 12 , 13 ). These skills include depth perception, 2D and 3D vision orientation, sensitive movements in limited environments ( 14 ), bimanual coordination, and hand-eye coordination ( 15 , 16 ). In fields such as chess, music, sports, and mathematics, studies on human performance have shown that attaining an expert performance level requires about 10,000 hours of focused practice ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…For this study, two scenarios were used which were developed for endoneurosurgery training programs ( Cagiltay et al, 2019 ). Each scenario includes some user tasks intended to improve certain endoscopic surgical skills like depth perception, left–right hand coordination and eye-hand coordination in a 3D simulated environment.…”
Section: Methodsmentioning
confidence: 99%
“…Four different scenarios simulating different surgical procedures in a virtual environment were designed in accordance with the feedback of expert surgeons from Hacettepe University Medical School with more than 30 years' experience in skull base surgery. Their educational evaluations including these scenarios also show some encouraging results for supporting surgical education programmes [23]. Each scenario contained different tasks to be performed to develop different skills among surgical residents, such as eye-hand coordination, fast tracking of objects, depth perception, effective use of surgical instruments, and simultaneous use of both hands.…”
Section: Rq2 Do the Algorithms Form Different Clusters?mentioning
confidence: 97%
“…Besides, several studies have been undertaken to investigate eye movements in order to support surgical training programmes, specifically to improve surgical simulations and needle insertion simulations to represent real-life environments, such as soft tissues [17]- [21]. These improvements on the techniques used for surgical simulations have several potential benefits for surgical training programmes in terms of providing support for skill assessment procedures [22] and helping candidate surgeons acquire the necessary skills [23]. Additionally, there is some evidence showing the benefits of better understanding the eye-movement events of surgical residents while they are performing surgical tasks in computer-based simulation environments [24].…”
Section: Introductionmentioning
confidence: 99%